Association mapping in rice: basic concepts and perspectives for molecular breeding. (3rd July 2018) - Verdeprado, Holden; Kretzschmar, Tobias; Begum, Hasina; Raghavan, Chitra; Joyce, Priya; Lakshmanan, Prakash; Cobb, Joshua N.; Collard, Bertrand C.Y.
ABSTRACT: In the last decade, association mapping (AM) has become a well-established method to detect genes and quantitative trait loci (QTLs) associated with agronomically important traits. The identification of a large number of single nucleotide polymorphisms (SNPs) from genome sequencing and concurrent development of high-throughput genotyping platforms has led to AM being widely used for a range of crops. These technologies have been used in rice ( Oryza sativa ) to explore the abundant diversity and there is enormous potential to identify novel QTLs for traits of interest. Due to the availability of cost-effective high-throughput SNP genotyping methods and rapid developments in rice genomics, it is inevitable that these AM approaches will become more popular in the future, especially in the context of genome-wide association studies (GWASs). In this paper, we review the fundamental concepts, critical considerations and limitations of AM focusing on rice, and reiterate the importance of accurate phenotypic data. We also include a section about connecting GWAS to molecular breeding, covering practical consideration for breeders, which is required to use GWAS results in actual rice molecular breeding programs and which has not received adequate attention in the scientific literature.